Adaptasi kepada budaya organisasi dan kompetensi komunikasi antara budaya pengurus Malaysia alam syarikat multimedia - Yaacob, Hashim Fauzy (Faculty of Management and Human Resources Development, 2007)
The main objective of the study is to identify the relationship between intercultural communication competence and adaptation towards organizational culture among Malaysian managers working for foreign multinational corporations in Malaysia. The study is based on the integration of anxiety/uncertainty management (AUM) theory by Gudykunst (1995), cross-cultural adaptation theory (COAT) by Yun Young Kim (2001), organizational culture model by Harris and Moran (1991) and the system theory. Integration of all these theories and model were made because there is no specific theory on intercultural communication competence and adaptation in an organizational context, and a theory on intercultural communication competence and adaptation towards the organizational culture. This survey research employed a self-administered questionnaire. A total of 212 respondents were selected randomly from multinational companies operating in Malaysia. A five-point Likert-item scales were used to measure (a) Malaysian managers' adaptation towards organizational culture (b) intercultural communication competence among Malaysian managers, and (c) Malaysian managers' perception of their interpersonal communication with expatriates. Descriptive and inferential analysis, namely frequency, mean, Pearson's correlation, partial correlation. multiple regression, and hierarchical regression were used to analyze the data. This research showed that the level of adaptation towards organizational culture. intercultural competence and interpersonal communication of Malaysian managers with expatriates is high, suggesting that they are culturally competent. Malaysian managers prefer integration rather than assimilation, separation or marginalization in adaptation towards organizational culture. The research also showed that there is a positive relationship between intercultural communication competence and adaptation to organizational culture. The dimensions of intercultural communication competence are knowledge, motivation and skills and overall intercultural communication competence contributes towards the adaptation into the organizational culture. This research however found that interpersonal communication with expatriates is not a moderating variable affecting the contribution of knowledge, motivation and skills on organizational culture adaptation, and overall intercultural communication competence. The study offer several suggestions which include the need for development of a theory specifically on intercultural competence and adaptation towards organizational culture.